Distribusi Nematoda Pucuk Putih Padi Aphelenchoides besseyi di Pulau Jawa - Diana, Didiet Rahayu (Jurnal Fitopatologi Indonesia, 2018)
Distribution of Rice White Tip Nematode Aphelenchoides besseyi in Java Island    Aphelenchoides besseyi is one of the most important rice seed borne nematode causing white tip disease in Indonesia.  The status of A. besseyi is considered as quarantine pest category A2, with limited distribution area in Java, Sumatera, and South Kalimantan). The aim of this research was to detect and identify A. besseyi from rice seed based on morphological, morphometry and molecular approaches and to determine its distribution in rice growing areas in Java. Rice seed samples, consisting of 26 varieties, were obtained from seed producers, seed distributors, and farmers in Java. Nematode extraction was done using Baermann method. Molecular identification was carried out by polymerase chain reaction and followed by DNA sequencing and nucleotide analysis. A. besseyi was detected from 74.32% of seed samples. A. besseyi was confirmed to be distributed in Lebak, Bogor, Sukabumi, Subang, Indramayu, Klaten, Sragen, Sukoharjo, Boyolali, Pati, Pemalang, Yogyakarta Sleman, Magetan, Blitar, Tuban, Gresik, Nganjuk, and Banyuwangi. Further nucleotide analysis showed that A. besseyi isolates from rice seed cv Ciherang (Yogyakarta) and cv IR 64 (Banyuwangi) have 99% homology to those from India, China, USA; and  98% homology to those from Taiwan.